Estratégias para transformação digital dos escritórios de contabilidade: a proposição de um framework - Oliveira, Jessica Benetti de (Universidade do Vale do Rio dos Sinos, 2021)
Changes have always been part of the people and companie’s life, it would not be different in the accounting context. Digital technologies have brought a new reality to this evolutionary process, in which many authors believe is taking place in a moment of digital transformation. Digital transformation is a process that manages the negative and positive results of the use of technologies and their impact on structural changes resulting in strategic responses. Considering the scenario presented, the issue of this study was to answer the question: what strategic guidelines should accounting firms follow to initiate a digital transformation? In order to address this question, the research aims to propose an artifact to guide the accouting offices in this process. This research is associated with the line of action of Innovation and Sustainability of the Professional Program in Management and Business (PPGN) and was developed through the methodology of Design Science Research. For the initial proposal of the framework, guidelines were sought in the literature and after this research, the artifact was validated in 3 different stages. Firstly, with academics, then with specialists in digital transformation and, finally, with accounting entrepreneurs who have already started their digital transformation process. At the end of each stage, the version of the artifact was incremented, arriving in a final framework composed of seven strategic guidelines. These guidelines are: 1) adherence to the company's strategy; 2) risk culture; 3) organizational culture for innovation; 4) organizational restructuring; 5) constant adoption of new digital technologies; 6) change in the service provided to the customer; and 7) communication with the customer. Among the theoretical contributions of the present study, some stand out that indicates that investment in new technologies is much more related to the cost of operating a new tool than to the financial cost, due to the demand for hours of implementation. Another contribution found was the importance of restructuring the pricing of services offered by the company and an analysis of whether or not to monetize the opportunities resulting from the adoption of digital technologies. In addition to the theoretical contributions, this research also makes managerial contributions. Among them, we highlight the final delivery of an artifact, developed and validated with experts on the subject in several aspects, so that accounting entrepreneurs can guide themselves in the moment of decision-making for the digital transformation of their offices. However, it should be noted that, in order to make a decision on a digital transformation process, the accounting entrepreneur must first have the clarity of his business strategy to then use this transformational process and enhance its results.
Keywords: Transformação digital; Empresário contábil; Design science research; Estratégia de transformação digital; Framework de transformação digital; Digital transformation; Accouting entrepreneur; Strategy to digital transformation; Digital transformation framework; ACCNPQ::Ciências Sociais Aplicadas::Administração